HIF - 1α as a marker of risk assessment for malignant transformation in oral submucous fibrosis: An immunohistochemical study - Kanika Sharma; Devi C Shetty; Ajit S Rathore; Saurabh A Juneja; Sonal Katyal; Ankaj Krishnatre (Wolters Kluwer Medknow Publications, 2022)
Background: Oral submucous fibrosis (OSMF) is a potentially malignant disorder associated with habit of chewing betel quid containing arecanut. Morphological features of OSMF especially fibrosis suggests a possibility of the hypoxic environment in diseased tissues. The adaptation of cells to hypoxia appears to be mediated via hypoxia inducible factor-1α (HIF-1α) which is also said to be associated with malignant transformation of epithelial cells in various other carcinomas like prostate and cervical carcinoma. Therefore, the main objective of this study was to investigate the role of HIF-1α in progression and malignant transformation of OSMF. Materials and Methods: The study group consisted of histo-pathologically diagnosed 30 cases of oral submucous fibrosis and 10 cases of OSCC were taken as control. The immunohistochemistry was carried out on neutral buffered formalin-fixed paraffin-embedded tissue sections by using the monoclonal antibody of HIF-1α. Statistical analysis was done using SPSS software version 2.0. Results: A gradual and significant rise in the expression of HIF-1α was observed in various grades of OSMF and OSCC cases. HIF 1α expression was increased in cases showing hylanization and constricted blood vessels. A cut off value of 39.6% of HIF-1α positive cells was determined statistically to categorize the cases into high risk and low risk group for malignant transformation. Conclusion: Overexpression of HIF-1α may contribute to the progression and malignant transformation of OSMF. Cases expressing more than 40% of HIF-1α positive cells are at a greater risk for malignant transformation.